2017
DOI: 10.1159/000458160
|View full text |Cite
|
Sign up to set email alerts
|

Improved Visual Outcome and Low Recurrence with Early Treatment with Intravitreal Anti-Vascular Endothelial Growth Factor in Myopic Choroidal Neovascularization

Abstract: Purpose: The aim of this study was to determine the correlation between the duration of myopic choroidal neovascularization (CNV) and treatment outcome after anti-vascular endothelial growth factor (VEGF) injections. Methods: We performed a retrospective review of treatment-naïve myopic CNV patients who were treated with anti-VEGF and followed for at least 24 months to identify factors predicting final outcome and recurrence. Results: Among 106 eyes, a shorter duration of CNV was a significant predictor of a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In the present study, we found that the recurrence rate was 20.2%, which was consistent with previous findings. Under no difference in treatment, the present study suggested that the duration of illness on initial diagnosis in the recurrence group was longer than that in the non-recurrence group, which was an independent risk factor for IgAV recurrence (P = 0.000), and consistent with findings of many other studies [23][24][25][26]. The reason for this finding may be that in autoimmune diseases, early treatment can promote the transformation from immune response involved by non-specific T cells and antibodies to that involved by specific T cells and antibodies as soon as possible, avoiding further tissue injury resulting from excessive activation of immune cells and release of more inflammatory factors [27].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we found that the recurrence rate was 20.2%, which was consistent with previous findings. Under no difference in treatment, the present study suggested that the duration of illness on initial diagnosis in the recurrence group was longer than that in the non-recurrence group, which was an independent risk factor for IgAV recurrence (P = 0.000), and consistent with findings of many other studies [23][24][25][26]. The reason for this finding may be that in autoimmune diseases, early treatment can promote the transformation from immune response involved by non-specific T cells and antibodies to that involved by specific T cells and antibodies as soon as possible, avoiding further tissue injury resulting from excessive activation of immune cells and release of more inflammatory factors [27].…”
Section: Discussionsupporting
confidence: 91%
“…Wakazono et al [25] reported that exudative AMD recurred in 43.7% of patients after aflibercept treatment. Moon et al [26] reported that 34.9% of patients with myopic CNV experienced recurrence, and two other studies reported that 23.3% and 22.7%, respectively, showed recurrence of CNV [27,28]. In the present study, the rate of recurrence of PCV was 59.7%, which is significantly higher than that of myopic CNV.…”
Section: Discussionsupporting
confidence: 43%
“…is percentage seems to be lower than in myopic CNV or neovascular AMD [17][18][19][20]. In fact, since CNV was secondary to an inflammatory aetiology, managing the primary disease with an anti-inflammatory/immunosuppressive approach allows better disease control, reducing recurrence and need for anti-VEGF injections.…”
Section: Discussionmentioning
confidence: 99%